Understanding the structure–activity relationship and performance of highly active novel ATRP catalysts. Issue 35 (19th August 2022) - Kröckert, Konstantin W.; Garg, Felix; Heinz, Michel V.; Lange, Justin; Simões, Patricia P.; Schmidt, Regina; Bienemann, Olga; Hoffmann, Alexander; Herres-Pawlis, Sonja
Abstract : Copper bromide complexes based on guanidine-quinolinyl and -pyridinyl ligands are suitable catalysts for atom transfer radical polymerisation (ATRP). Changes in the ligand design influence the complex geometry and their catalytic activity. Abstract : Copper bromide complexes based on a series of substituted guanidine-quinolinyl and -pyridinyl ligands are reported. The ligand systems were chosen based on the large variation with regard to their flexibility in the backbone, different guanidine moieties and influence by electron density donating groups. Relationships between the molecular structures and spectroscopic and electronic properties are described. Beside the expected increase in activity by substituting the 4-position (NMe2 vs . H), we showed that a higher flexibility, such as TMG vs . DMEG moiety, leads to a better stabilsiation of the copper(ii ) complex. Due to the correlation of the potentials and K ATRP values, the catalyst based on the ligand TMGm4NMe2 py is the most active copper complex for ATRP with a bidentate ligand system. The combination of the strong donating abilities of dimethylamine pyridinyl, the donor properties of the TMG substituent, and the improved flexibility due to the methylene bridging unit leads to high activity. With all NMe2 -substituted systems standard ATRP experiments were conducted and with more active NMe2 -substituted pyridinyl systems, ICAR ATRP experiments of styrene were conducted. Low dispersities and ideal molar masses have been achieved.